2020
DOI: 10.3389/fmicb.2020.557435
|View full text |Cite
|
Sign up to set email alerts
|

A Mixture of D-Amino Acids Enhances the Biocidal Efficacy of CMIT/MIT Against Corrosive Vibrio harveyi Biofilm

Abstract: Biocides are widely used for the mitigation of microbial contamination, especially in the field of the aviation fuel industry. However, the long-term use of biocide has raised the concerns regarding the environmental contamination and microbial drug resistance. In this study, the effect of a mixture of D-amino acids (D-tyrosine and D-methionine) on the enhancement of the bactericidal effect of 5-Chloro-2-Methyl-4-isothiazolin-3one/2-Methyl-2H-isothiazole-3-one (CMIT/MIT) against corrosive Vibrio harveyi biofil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Biofilms are almost composed of EPS, extracellular enzymes, and extracellular DNA, enabling bacteria to adhere to living or nonliving surfaces. Therefore, the effect of compound C 1 on biofilm formation was spontaneously proposed and analyzed by crystal violet quantification assays. As depicted in Figure C , compared with control samples, compound C 1 at a dosage of 2.2 μg mL –1 was found to reduce 51.3% biofilm formation of Xoo cells.…”
Section: Resultsmentioning
confidence: 99%
“…Biofilms are almost composed of EPS, extracellular enzymes, and extracellular DNA, enabling bacteria to adhere to living or nonliving surfaces. Therefore, the effect of compound C 1 on biofilm formation was spontaneously proposed and analyzed by crystal violet quantification assays. As depicted in Figure C , compared with control samples, compound C 1 at a dosage of 2.2 μg mL –1 was found to reduce 51.3% biofilm formation of Xoo cells.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al designed a kind of micelle, and the D-Tyrosine loaded on the micelle was released in an acidic environment to decompose the biofilm matrix [248]. Most studies have demonstrated the great clinical value of D-type amino acid, a dispersal factor of bacteria (Figure 13a) [249,250]. Furthermore, Olivier et al first studied the effect of human hormone atrial natriuretic peptide (hANP) on formation and dispersion of P. aeruginosa biofilm [251].…”
Section: Active Dispersion Biofilmmentioning
confidence: 99%
“…Microbial growth inhibition usually takes a few minutes and the cell death might take several hours (Morley et al 2005;Kucera 2019;Silva et al 2020). The slow kinetics of inactivation can be overcome by increasing the biocide concentration or adding surfactants (Kucera 2019;Liu et al 2020). Notably, MIT presents high antimicrobial efficacy against a wide range of microorganisms, such as bacteria, algae, and fungi (Williams 2006;Majamaa et al 2011;Kucera 2015).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In the RO industry, MIT is frequently applied for both membrane storage and cleaning. This indicates that this chemical cannot only inhibit microbial growth but also it can remove mature biofilms by disrupting the EPS matrix of the biofilm (Kucera 2015;Kucera 2019;Liu et al 2020). Therefore, MIT is capable of preventing and controlling the biofouling of polyamide membranes.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%